Análise da taxa de subsidência da Bacia de Campos nas proximidades do Lineamento Alegre - (:unkn) unknown (Universidade Federal do Pampa, 2015)
Passive continental margin sedimentary basins are characterized by two subsidence stages. During the rift phase, subsidence is accelerated by crustal stretching processes (mechanic subsidence). After the rift phase, subsidence rates are relatively smaller, defined by thermal subsidence. Sedimentary basins Geohistory Analysis allows reconstruct subsidence rates through time in one point (1D), along a cross-section (2D) or in a volume (3D). This procedure results in accumulation curves for compacted and uncompacted sediment sequences. Backstripping technique consists in an isostatic balance which allow the isolation of the sedimentary load from the total subsidence component and to obtain the tectonic subsidence. The tectonic subsidence is influenced by three variables in function of time: i) sediments deposited y(t), ii) water column depth Wd(t), and iii) global sea level variations ∆SL(t). In this work, it was analyzed the subsidence history of Campos Basin. This basin is located at the Brazilian continental margin, and have an area of circa one hundred thousand Km². It is limited to the south by the Cabo Frio High, which separates Campos from Santos Basins, and to the north by the Vitória High, separating Campos from Espírito Santo Basins. Basin subsidence history was defined in two wells, provided by ANP. The wells were labeled 1–BRSA–797–RJS e 3GP–002A–RJS and located near the city of Campos, Rio de Janeiro. The selected wells occur to the NE and SW directions of an important structural feature in the SE Brazil, named Alegre Lineament. Based on the subsidence history analysis it is possible to determine quantitatively and represent graphically the compacted sedimentary packages accumulation curves through time and latter, with the correction of the subsidence history, it is obtained the curves related to the uncompacted sedimentary thickness. The Backstripping tool allow removing the sedimentary load component and to obtain the curves that correspond to the tectonic subsidence of Campos Basin at the vicinities of Alegre Lineament. Distinct subsidence curves are defined and present variations in the subsidence from 30 Ma, showing diferential subsidence rates between the two wells. This reflects distinct evolution between the SW and NE blocks separated by the Alegre Lineament.
Keywords: Bacia de Campos; Análise de Subsidência; História de Subsidência; Backstripping; Campos Basin; Subsidence Analysis; CNPQ::CIENCIAS EXATAS E DA TERRA